A etnogeomorfologia da bacia hidrográfica do rio Poti, Ceará e Piauí - Ribeiro, Karoline Veloso (2024)
Ethnogeomorphology is essential in understanding the geomorphological classification in relation to the way traditional populations perceive and interpret the landscape around them. In this context, this study aimed to systematize the ethnogeomorphological taxonomies, based on the knowledge of the key informants of communities in the low, middle and upper river courses of the Poti River basin, in order to identify the relief units, incorporating the ethnogeomorphological classification, based on topographic profiles. The research took place in the communities of Caraíba (Lagoa do Piauí/PI), Goiabeira, Fortaleza, Virtude and Lembrança (Novo Santo Antônio/PI) and Santo Onofre (Novo Oriente/CE). It is noteworthy that the choice of communities corresponded to those whose river sector corresponded to the highest elevation. The methodology was based on the theoretical basis, preparation and analysis of cartographic materials, application of semi-structured interview forms to rural producers/riverside dwellers and data analysis by the mixed approach method. To define the sample universe, a non-probabilistic procedure was used, totaling 69 families interviewed, including all the residences of the communities studied, making a sketch and, finally, elaborating a topographic profile of the communities studied with the ethnogeomorphological classification. In the lower river course, the rural/riverine producers identified and classified the relief units of: "Baixada or Baixa" and "Morro, Serra or Carrasco. Although there were differences between them, the taxonomies used by the key informants were quite similar. With regard to the fluvial dynamics, the participants highlight that the construction of the Flor do Campo Dam (CE) interfered in the flow of the Poti River and that the predatory practice of human action, such as the removal of sand from the riverbed, potentiates significant changes in it and, consequently, in its dynamics, in addition to contributing to the scarcity of this natural resource. In view of the above, the great accumulation of knowledge is evidenced, considered vital for rural producers/riverside dwellers who live in tune with the fluvial dynamics of the Poti River.